Impact Analysis of Large-Scale Environmental Spot Inspection Policy on Green Innovation: Evidence From China - Chen, Bo; Ren, Meitong; Chen, Liye (Frontiers in Environmental Science, 2021)
The spot inspection policy has been widely applied in environmental protection in China. This paper collects environmental enforcement announcements and green patent data published by Chinese government agencies from 2006 to 2015. First, it studies the impact of spot inspection on green innovation with the spatial Durbin model. Then, it analyzes spatial heterogeneity according to the eastern, central, and western regions including 29 provinces. The spot inspection policy significantly increases the green innovation of a current region with a negative spillover effect on neighboring regions. Even though this policy has the best performance in the eastern region, it leads to pollution transfer into the western region, while being ineffective in the central region. Further, analysis on the spatial spillover effects of the 29 provinces proves that 21 provinces have a positive spillover effect, while 8 provinces have a negative spillover effect. The research study shows that although spot inspection is generally beneficial to green innovation, pollution transfer and policy failure exist because of spatial heterogeneity.